Heat transfer - Holman, J. P. (Jack Philip) (New York : McGraw-Hill, 2002)
Introduction; steady - state conduction - one dimension; steady - state conduction - multiple dimensions; unsteady - state conduction...
Includes bibliographical references and index.
Keywords: Heat; Heat -- Transmission